Model Sistem Penunjang Keputusan Untuk Menentukan Jurusan Calon Siswa Baru Menggunakan Metode Profile Matching Pada SMK XYZ - Agus Umar Hamdani; Savira Aprilya (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
SMK XYZ is a Vocational School based on technology and located in South Jakarta. This school has several majors, namely Software Engineering (RPL), Network Computer Engineering (TKJ) and Multimedia (MM). Every new school year, new students of new students who register increases. However, there are problems encountered in the process of selecting student majors, namely inaccurate decision making, there is no ranking, decision making has not used the method and is still using Microsoft Excel, so it requires quite a long time in determining student majors. The purpose of this study is to create a decision support system that is expected to help in determining the right majors for new students in SMK XYZ in accordance with the criteria set by SMK XYZ. This research resulted in a decision support system using the Profile Matching Method as a method for determining alternative final values. Reports produced by this system are value reports that contain the values calculated by students' grades. This decision support system was created using MySQL as a database and Microsoft Visual Studio 2008 as a system creation tool. With this support system, it can help the student in processing data and decision making in order to determine student majors.